Understanding query complexity and its implications for energy-efficient web search - Bragg, Emily; Guevara, Marisabel; Lee, Benjamin C. (Proceedings of the 2013 International Symposium on Low Power Electronics and Design, 2013)
Today's largest datacenters dissipate megawatts of power. Efficiency is rapidly becoming the primary determinant of datacenter capability. To understand microarchitectural factors that affect efficiency, we must study datacenter workloads.